Revision of Pygoda Amyot & Serville, 1843 stat. rest. (Heteroptera: Pentatomidae: Edessinae) with description of four new species - Fernandes, Jose Antonio Marin; Nascimento, Agata Tyanne Silva; Nunes, Benedito Mendes (Zootaxa, 2018)
Edessa is the largest genus of Edessinae and comprises five subgenera: Edessa, Aceratodes, Dorypleura, Hypoxys and Pygoda. Systematics of Edessa is very confusing due to several factors, among them, large number of species and vague diagnosis to the subgenera. In this work we continue revising Edessa elevating Pygoda to genus level based in morphological characters: pronotal angles short and acute. Abdominal segment VII developed posteriorly and at least 1.5 longer than wide at the base. Males with pygophore large in relation to body size when compared with other edessines. Phallus large, constricted distally and showing a remarkable ventral development. Females with capsula seminalis large in comparison with other edessines. Distal part of the ductus receptaculi sclerotized. Pars intermedialis with sclerotized part bigger than membranous part. This genus comprises nine species: the type species Pygoda polyta, four species originally described in Edessa—E. irrorata, E. thoracica, E. expolita and E. civilis, and four new species—P. amianta, P. variegata, P. poecila and P. ramosa. Diagnosis, illustration of the internal genitalia from males and females, photographs of the external genitalia from both sexes, body in dorsal and ventral view, and distribution map are provided. A key to the species of Pygoda is also provided. The lectotypes of Edessa irrorata, Pentatoma polyta, Edessa nervosa, Edessa civilis and Edessa thoracica are here designated.